1968
DOI: 10.1088/0022-3727/1/10/309
|View full text |Cite
|
Sign up to set email alerts
|

Strain induced in yttrium iron garnet by various milling treatments

Abstract: This paper presents the results of measurements of the changes in strain, as determined from x-ray diffraction line broadening, stored strain energy, particle shape, size and size distribution in samples of yttrium iron garnet powder brought about by a variety of milling treatments. For similar starting material the strain induced by the various milling procedures was found to vary by two orders of magnitude. An example is given of the build-up of strain and the accompanying changes in particle characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

1969
1969
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The estimated rms strain from XRD results were used in the calculation of strain energy per mole [42] as follows:…”
Section: Free Energy Of Finite Size In Ag and Bi Mechanical Mixturementioning
confidence: 99%
“…The estimated rms strain from XRD results were used in the calculation of strain energy per mole [42] as follows:…”
Section: Free Energy Of Finite Size In Ag and Bi Mechanical Mixturementioning
confidence: 99%
“…Koepke and Stokes (106) on magnesium oxide single crystals; Richards and Greenham (169) on the strain energy in garnet particles; Schneider (181,182) on effects in sand and salt with different mills and milling atmospheres; Ogura and Sobue (155) on changes in microcrystalline cellulose; Krauth and Tomandl (777) on detection of changes in iron oxides by the Mossbauer effect; and Krauth (7 72) on changes in TaC, VC, and ZrN powders by pressing and grinding. A practical application in connection with changes in the magnetic properties of iron oxide is reported by Karasinska (97), and Vonszant et al (204) report the activation of titanomagnetite by vibrational grinding.…”
Section: Crystal and Chemical Changes In Fine Grindingmentioning
confidence: 99%
“…They showed that microstrains were an important factor influencing the temperature and time of sintering. Most materials are ball milled in preparation for sintering, and Richards & Greenham (1968) have shown that the vibratory ball milling of yttrium garnet produces sufficient residual strain energy to be significant in comparison with the surface free energy. Lewis & Northwood (1968) have shown that microstrains produce a change in the electrode potential of copper wires and a corresponding reduction of corrosion resistance.…”
Section: Effects Of Microstrainsmentioning
confidence: 99%